MEDIA PEMBELAJARAN INTERAKTIF BERBASIS EDUTAINMENT - Muhammad Ibnu Sa'ad; Heny Pratiwi; Ahmad Abul Khair (BEduManagers Journal : Borneo Educational Management and Research Journal, 2023)
This educational entertainment-based interactive learning media aims to maximize the teaching and learning process to make it easier and more enjoyable so that it can increase students' interest in learning, especially financial literacy, 3D animation material. Apart from that, teachers can also create questions for students to work on without having to correct them manually because of this system. equipped with an automatic error correction feature based on answers made by the teacher and an educational entertainment system on this website. It is also equipped with mini flash games so that the site content becomes more diverse, and the material is equipped with animation. Content updates can be done dynamically via the admin panel. This educational entertainment-based interactive learning media was developed using the Prototype system development methodology and system development tools using UML (Unifield Modeling Language). In developing this educational entertainment website, the programming languages PHP, HTML, JavaScript, JQuery MySQL Database, and Sublime Text were used as editors. text and Adobe Flash Professional CS6 as image editor. From the results of this research, an edutainment website was created which contains learning material features in the form of animated images, video tutorials about 3D animation, photos of teaching and learning activities for students majoring in multimedia engineering, educational games, discussion forums and multiple choice questions.